Pengaruh Budaya Organisasi, Pelatihan, dan Gaya Kepemimpinan terhadap Kinerja Karyawan - Wulandari, Wulandari; Nurimansjah, Ris Akril; Azis, Nur; Yuliana, Rachma; Chandra, Dharnita (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study aims to investigate how organizational culture, training, and leadership style influence employee performance at PT PS in Solo City. This study uses a causal associative approach and quantitative methods. Employees working at PT PS in Solo City served as the population. The sample consisted of 89 employees selected using a census. A survey method was used for data collection, with employees given questionnaires to complete. SmartPLS was used for data analysis, which employed partial least squares-structural equation modeling (PLS-SEM). Based on the research findings, organizational culture, training, and leadership style partially influence employee performance at PT PS in Solo City. Simultaneously, organizational culture, training, and leadership style significantly influence employee performance at PT PS in Solo City.